The Effect of MIME Game Toward Students’ Vocabulary Mastery at the Eighth Grade of SMPN 1 Malingping Lebak Banten in Academic Year 2023/2024 - Nopiyanti, Selpi; Gumelar, Ridzki Elang; Riandi (CV. Kurnia Grup, 2024)
This research aimed to investigate the significant effect of Mime game towards vocabulary mastery. This approach was quantitative approach Quasi-experimental approach with the test method in collecting data. The research was carried out in several stages starting from validation including pre-test and post-test after that it would find the results of class VIII students. The results showed that students' interest in learning language in class VIII was in the medium category, the population of this study amounted to 258 students and the sample taken in this research amounted to 66 students consisting of two different classes 33 experimental class students and 33 control class students. The experimental class used a Mime game and the control class used a board game. Based on the results of data analysis, it was found that the average pre-test and post-test of the experimental class and control class were different and for the t-test results a significance value of 0.000 < a = 0.05 was obtained. This results indicate that the alternative hypothesis is accepted and the null hypothesis is rejected. Based on the results of this research, there is a significant effect of Mime game on students vocabulary mastery.